Strategi Kepemimpinan Transformasional Kepala Sekolah dalam Membangun Budaya Sekolah: Studi Pustaka - Supriyadi, Astia Meilinda; Kurnaningsih, Yari Dwi; Satyawati, Sophia Tri (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2026)
School culture is understood as a set of values, norms, beliefs, and collective practices that shape organizational behavior. In situations of educational policy change, transformational leadership is seen as capable of encouraging value transformation, strengthening shared commitment, and fostering school culture. This study uses a qualitative approach with a literature study method. Data were collected through searching and analyzing various scientific articles relevant to the themes of transformational leadership, school culture, and school leadership. The literature sources came from accredited national journals and international journals published in the period 2016–2026. The results of the study show that the principal's transformational leadership strategy is reflected through exemplary values and strengthening discipline, articulating the school's vision, intellectual stimulation through professional learning communities, and a relational approach that pays attention to the needs and professional development of teachers. The process of shaping school culture involves instilling values, integrating them into the curriculum and school programs, and setting an example for leaders and teachers. These findings confirm that transformational leadership contributes to building a collaborative, reflective school culture that is oriented toward improving the quality of education.